KOMUNIKASI PENYADARAN DALAM PEMBERDAYAAN IBU RUMAH TANGGA MELALUI DANA CORPORATE SOCIAL RESPONSIBILITY - Muhammad Riduansyah Syafari (Universitas Lambung Mangkurat, 2019)
The activity of awareness communication in empowering housewives through the budget of corporate social responsibility in Maburai village, Tabalong regency, is quite unique. The research method used is qualitative approach with descriptive type using primary and secondary data sources. Data collection techniques used are observation, interviews and documentation. The results of the study shows that awareness communication conducted by the pattern of direct visits to small medium enterprises (SMEs) which have been successful from scratch then continued with the dialogical discussion of post-visit is quite effective. The pattern is able to create entrepreneurial awareness and motivation for housewives in Marburai village to have desire to make change in the family's economic conditions and make it as an alternative source of business in the future.